Management of Meige syndrome with bilateral trigeminal and facial nerves combing - Ying, Tingting; Wang, Haopeng; Tang, Yinda; Zhao, Hua; Cai, Xiaomin; Shen, Yiman; Wang, Baimiao; Zhu, Wanchun; Zhou, Ping; Zhang, Xin; Zhong, Jun; Wang, Xinjun; et al. (Frontiers in Neurology, 2024)
Objective: Meige syndrome (MS) is an adult-onset segmental dystonia and there is no satisfactory remedy for this syndrome. Our team developed a novel surgical approach named bilateral trigeminal/facial nerves combing (BTFC). This study aimed to evaluate the outcome of those patients following BFTC (Clinical trial registry number: ChiCTR2000033481). Method: We assigned 22 patients who had MS to undergo BTFC. Primary outcome was the movements subscale of Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS-M) at month 12 postoperatively. Second outcome was evaluated by Mos 36-item Short Form Health Survey (SF-36), dysfunction of Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS-D), and subitem scores of BFMDRS-M. Safety outcomes was the House Brackmann (HB) functional grading score and Visual analogue scale (VAS) of facial numbness.At the final follow-up of 12 months, the BFMDRS-M showed a mean improvement of 70.7% from baseline. Mean scores of the BFMDRS-M submotor (including eyes, mouth, and speech/swallowing) improved by 65.6%, 81.00%, and 60%, respectively. The median score of the total BFMDRS-D score were 0.70±1.17 compared with 1.86±2.21 at baseline. There were no serious operative complications in this population. The quality of life of the patients was significantly improved (P＜0.05).Conclusions BFTC demonstrated to be effective in relieving the symptoms of Meige syndrome and provided a new alternative treatment for patients who have failed to respond to medications, botulinum toxin injections and DBS.